2005
DOI: 10.1186/cc3023
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction Few studies have evaluated urinary tract infections (UTIs) specifically acquired within intensive care units (ICUs), and the effect of such infections on patient outcome is unclear. The objectives of this study were to describe the occurrence, microbiology, and risk factors for acquiring UTIs in the ICU and to determine whether these infections independently increase mortality. Methods A surveillance cohort study was conducted among all adults admitted to multi-system and cardiovascular surgery IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…Bacteriuria was considered to be colonization if no clinical signs suggestive of UTI were noted (no fever and no urine symptoms). In women, cystitis and pyelonephritis were graded according to the clinical criteria of the European Urology Association [2,3,15]. In men, the clinical signs of UTI are heterogeneous, and little consensus has been reached regarding their classification into cystitis, pyelonephritis or prostatitis [4,16].…”
Section: Urinary Tract Colonization and Infectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bacteriuria was considered to be colonization if no clinical signs suggestive of UTI were noted (no fever and no urine symptoms). In women, cystitis and pyelonephritis were graded according to the clinical criteria of the European Urology Association [2,3,15]. In men, the clinical signs of UTI are heterogeneous, and little consensus has been reached regarding their classification into cystitis, pyelonephritis or prostatitis [4,16].…”
Section: Urinary Tract Colonization and Infectionsmentioning
confidence: 99%
“…We therefore decided to group these together into a single category of male UTI. A patient was considered to be suffering from a nosocomial UTI if this met the French clinical definition of care-related infections: occurrence of a UTI 48 h after hospital admission [3,17].…”
Section: Urinary Tract Colonization and Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the organisms can also cause serious invasive infections, including infections of the liver and lung, brain abscesses, bacteraemia, endocarditis and intra-abdominal infections Rashid et al, 2007). In a recent study, members of the SAG were identified as the most frequent cause of invasive pyogenic streptococcal infections in Canada (Laupland et al, 2006). SAG are generally considered to be susceptible to penicillin, other b-lactam antibiotics and macrolides, but resistant strains have been reported (Aracil et al, 1999;Limia et al, 1999;Tracy et al, 2001).…”
Section: Introductionmentioning
confidence: 99%